2020
DOI: 10.1021/jacs.0c08254
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic Insight into the Stereoselective Cationic Polymerization of Vinyl Ethers

Abstract: The control of the tacticity of synthetic polymers enables the realization of emergent physical properties from readily available starting materials. While stereodefined polymers derived from nonpolar vinyl monomers can be efficiently prepared using early transition metal catalysts, general methods for the stereoselective polymerization of polar vinyl monomers remain underdeveloped. We recently demonstrated asymmetric ion pairing catalysis as an effective approach to achieve stereoselective cationic polymeriza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
40
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(43 citation statements)
references
References 96 publications
1
40
0
Order By: Relevance
“…Inspired by asymmetric ion‐pair catalysis, the Leibfarth group [ 104,105 ] demonstrated that the combination of Ti‐catalyst and chiral 1,1′‐bi‐2‐naphthol (BINOL)‐based phosphoric acid as a ligand enabled stereoselective polymerization ( Figure A), providing a range of isotactic PVEs with high degrees of isotacticity at −78 °C with several hours of reaction time. The obtained stereocontrolled PVEs exhibit attractive properties.…”
Section: Emerging Initiation/controlling Systems For Lcpmentioning
confidence: 99%
See 1 more Smart Citation
“…Inspired by asymmetric ion‐pair catalysis, the Leibfarth group [ 104,105 ] demonstrated that the combination of Ti‐catalyst and chiral 1,1′‐bi‐2‐naphthol (BINOL)‐based phosphoric acid as a ligand enabled stereoselective polymerization ( Figure A), providing a range of isotactic PVEs with high degrees of isotacticity at −78 °C with several hours of reaction time. The obtained stereocontrolled PVEs exhibit attractive properties.…”
Section: Emerging Initiation/controlling Systems For Lcpmentioning
confidence: 99%
“…Reproduced with permission. [ 104 ] Copyright 2020, American Chemistry Society. B) ɑ,ɑ,ɑ′,ɑ′‐tetraaryl‐1,3‐dioxolane‐4,5‐dimethanol (TADDOL); Reproduced with permission.…”
Section: Emerging Initiation/controlling Systems For Lcpmentioning
confidence: 99%
“…Nuclear magnetic resonance (NMR) was recorded with an Advanced III 400 MHz Bruker spectrometer and an Advanced III 600 MHz spectrometer at 25 °C. 1 H NMR signals were measured relative to the signal for residual chloroform (7.26 ppm) in deuterochloroform (CDCl3), are reported in δ units, parts per million (ppm). 19 F NMR signals are reported in ppm units.…”
Section: Methodsmentioning
confidence: 99%
“…19 F NMR signals are reported in ppm units. 1 H-19 F NMR signals were reported in ppm units. Sizeexclusion chromatography (SEC) measurements were performed on an Agilent 1100 system equipped with a G1310A pump and a G1362A refractive index detector using THF as the eluant (1.0 mL/min at 35 ºC).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation